PROBIOTICS: LIVING MEDICINES IN HEALTH MAINTENANCE AND DISEASE PREVENTION - WADHER K.J; MAHORE; J.G; UMEKAR; M.J (International Journal of Pharma and Bio Sciences, 2010)
Probiotics are defined by the world health organization as live organisms, when taken in sufficient amounts; provide a benefit to human health. The use of probiotics in antibiotic resistance is termed microbial interference therapy. With increasing understanding that beneficial microbes are required for health, probiotics may become a common therapeutic tool used by health care practitioners in the near future. This review is about probiotics features, mechanisms of action, Composition, Clinical applications such as anti-diarrheal, Immune Enhancement, Anticancer, Anti-inflammatory, Lactose intolerance, Dysbacteriosis etc. With the current focus on disease prevention and the quest for optimal health at all ages, the future of probiotics is more promising